Analyses of the relationship between sources of sport-confidence and long term athletes` development in Nigeria - Adegbesan, O.; Pindar, M. N.; Adewunmi, C. M. (International Journal of Coaching Science, 2018)
The connection between athletes` development and sport confidence is gaining prominence in sport science literature. This connection with sport confidence is rarely research on like other psychological variables within this study environment, therefore our focus in this study was the examination of the relationship and whether the sport confidence sources can contribute positively to athletes` sport development. The participants used for this study were male (85) and female (48) athletes purposively drawn from football, basketball, swimming, tennis, table tennis, volleyball, hockey, hand ball and track and field athletics. Their mean age was (19.14, SD 5.12). Data was collected with the Sources of Sport Confidence Questionnaire and the Long Term Athlete Development Questionnaire. Internal consistency of both instruments were above the Nunnally criteria (r=.70). Statistical tools of Pearson product moment correlation and multiple regression model were used to analyse data collected at 0.05 level of significance. The results showed significant positive relationships between the sport confidence and athlete development variables. Further result showed significant composite effect of all the sources of sport confidence variables on athlete` development. While vicarious experience and situational favorableness components of the sport confidence did not relatively contribute significantly to the athletes` development. Sport-confidence construct has primarily been investigated within Bandura`s self-efficacy theoretical model. This approach undoubtedly has enhanced knowledge and facilitated the development of applied interventions at different stages of athletes` identification and development. Our finding suggests that the sources of sport confidence has a positive and moderate correlation with athletes` development. The sport confidence variables also compositely influenced athletes` development.